Analisis Beberapa Faktor Yang Berpengaruh Terhadap Jumlah Pengangguran Kabupaten/Kota Di Provinsi Bali - Sirait, Novlin; Marhaeni, A A I N (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Unemployment in the province of Bali each year in which fluctuated in 2003 and 2005 is the number of unemployed during the previous 10-year period, the unemployment rate may cause bad impact on the economy of Bali, because it can cause a variety of social and cultural issues such as poverty, crime and other. In fact, economic growth, education levels within a period of 10 years Bali has increased when in accordance with economic theory should be able to absorb the existing workforce. This research aims: 1) to determine the effect of economic growth, minimum wage, and education level either simultaneously or partially on the number of unemployed districts/cities in Provinces Bali. 2) To determine the variables that affect the number of unemployed dominant districts/cities in the province of Bali. The research was conducted in the province of Bali which divided the eight regencies and one city by using data over a period of 7 years, as the data retrieval The studies sampled using a purposive sampling method and using 63 data points as a sample. Data collected through non-participant observation. The data analysis technique used is multiple linear regression. Based on the analysis simultaneously, it was found that the growth of the economy, and the regional minimum wage levels significantly affect unemployment districts / municipalities in the province of Bali. Testing is done by comparing the partial count t and t table or view its significance to the 95 percent level of confidence gained that real economic growth positively, negatively affect regional minimum wages significantly affect unemployment districts / municipalities in the province of Bali, while negative real levels of education, and economic growth have the most dominant effect on unemployment districts / municipalities in the province of Bali. The study is expected to be useful for the government in decision-acquired sufficient regarding labor issues in particular the problem of unemployment. The studies are expected to be useful in future studies as references and can develop further addition of variables
Keywords: employment, unemployment, economic growth, education, and the minimum wage